Soil particle size fractions harbour distinct microbial communities and differ in potential for microbial mineralisation of organic pollutants - Hemkemeyer, Michael; Christensen, Bent T.; Martens, Rainer; Tebbe, Christoph C. (Soil biology & biochemistry, 2015)
Due to differences in mineralogical composition and organic matter density, soil particle size fractions (PSF) provide different surface properties and micro-environments, which may affect the adsorption of chemicals and select for distinct microbial communities. Using soils from a long-term fertilisation experiment, we examined the structural diversity of microbial communities associated with different PSF and their potential to mineralise two organic pollutants (phenol and 2,4-dichlorophenol (DCP)). The soils were taken from 0 to 18 cm depth of arable field plots that have been kept unfertilised (UNF), mineral fertilised (NPK), or treated with animal manure (AM) for 117 years. Sand, including particulate organic matter (POM), coarse silt, fine silt, and clay were isolated by gentle ultra-sonication, wet-sieving and centrifugation. Animal manuring increased the abundance of the three microbial domains Bacteria, Archaea and Fungi, with coarse silt being most responsive. The impact of manuring declined with decreasing particle size. Genetic profiling indicated that the composition of the bacterial communities was primarily shaped by soil particle size classes, while archaea responded predominantly to fertilisation. Particle size as well as fertilisation was equally important in structuring the fungal communities. All PSF showed capacity for phenol mineralisation with rates correlating negatively with particle size (except for the sand-POM fraction), and long-term fertilisation enhanced the mineralisation potential. In contrast, DCP mineralisation was associated with the clay fraction only and was highest for soil treated with mineral fertiliser. This study demonstrates that PSF harbour structurally distinct microbial communities with different functional potentials for mineralising organic pollutants. •Soil fractionated into particle size fractions (PSF) by ultrasonication and sieving.•PSF-attached cells remained metabolically active.•Each PSF harboured a characteristic microbial diversity.•Long term fertilization affected microbes stronger at larger than at smaller PSF.•Phenol was mineralized by microbes from all PSF, 2,4-dichlorophenol only from clay.